Reaction mechanism and kinetics for N2 reduction to ammonia on the Fe–Ru based dual-atom catalyst. Issue 43 (24th October 2022) - Rehman, Faisal; Kwon, Soonho; Hossain, Md Delowar; Musgrave III, Charles B.; Goddard III, William A.; Luo, Zhengtang
Abstract : To understand the reaction mechanism and kinetics of N2 reduction reaction and competing hydrogen evolution reaction on the dual-atom catalyst as a function of applied potential by applying the Grand canonical potential kinetics. Abstract : Environmental and energy considerations demand that the Haber-Bosch process for reducing N2 to NH3 be replaced with electrochemical ammonia synthesis where the H atoms come from water instead of from H2 . But a practical realization of electrochemical N2 reduction reaction (NRR) requires the development of new generation electrocatalysts with low overpotential and high Faraday efficiency (FE). A major problem here is that the hydrogen evolution reaction (HER) competes with NRR. Herein, we consider new generation dual-site catalysts involving two different metals incorporated into a novel two-dimensional C3 N–C2 N heterostructure that provides a high concentration of well-defined but isolated active sites that bind two distinct metal atoms in a framework that facilitates electron transfer. We report here the mechanism and predicted kinetics as a function of applied potential for both NRR and HER for the (Fe–Ru)/C3 N–C2 N dual atom catalyst. These calculations employ the grand canonical potential kinetics (GCP-K) methodology to predict reaction free energies and reaction barriers as a function of applied potential. The rates are then used in a microkinetic model to predict the turn-over-frequencies (TOF) as a function of applied potential. At U = 0 V, the FE for NRR is 93%, but the current is only 2.0 mA cm −2 . The onset potential (at 10 mA cm −2 ) for ammonia on Fe–Ru/C3 N–C2 N is −0.22 VRHE . This leads to a calculated TOF of 434 h −1 per Fe–Ru site. We expect that the mechanisms for NRR and HER developed here will help lead to new generations of NRR with high TOF and FE.